COVID‐19 risk in elective surgery during a second wave: a prospective cohort study. Issue 1 (21st January 2021) - Myles, Paul S.; Wallace, Sophie; Story, David A.; Brown, Wendy; Cheng, Allen C.; Forbes, Andrew; Sidiropoulos, Sofia; Davidson, Andrew; Tan, Niki; Jeffreys, Andrew; Hodgson, Russell; Scott, David A.; et al.
Abstract : The prevalence of SARS‐coronavirus‐2 in asymptomatic elective surgical patients during a second wave was approximately 1 in 833. Given the very low likelihood of coronavirus transmission and with existing current hospital capacity, elective surgery can recommence at near‐normal levels. Abstract: Background: The COVID‐19 pandemic has greatly affected access to elective surgery, largely because of concerns for patients and healthcare workers. A return to normal surgery workflow depends on the prevalence and transmission of coronavirus in elective surgical patients. The aim of this study was to determine the prevalence of active SARS‐coronavirus‐2 infection during a second wave among patients admitted to hospital for elective surgery in Victoria. Methods: Prospective cohort study across eight hospitals in Victoria during July–August 2020 was conducted enrolling adults and children admitted to hospital for elective surgery or interventional procedure requiring general anaesthesia. Study outcomes included a positive polymerase chain reaction (PCR) test for SARS‐CoV‐2 in the preoperative period (primary outcome), and for those with a negative test preoperatively, the incidence of a positive PCR test for SARS‐CoV‐2 in the post‐operative period. Results: We enrolled 4965 elective adult and paediatric surgical patients from 15 July to 31 August 2020. Four patients screened negative on questionnaire but had a positive PCR test for coronavirus, resulting in a Bayesian estimated prevalence of 0.12% (95% probability interval 0–0.26%). There were no reports of healthcare worker infections linked to elective surgery during and up to 2 weeks after the study period. Conclusion: The prevalence of SARS‐CoV‐2 in asymptomatic elective surgical patients during a second wave was approximately 1 in 833. Given the very low likelihood of coronavirus transmission, and with existing current hospital capacity, recommencement of elective surgery should be considered. A coronavirus screening checklist should be mandated for surgical patients.